Transformasi Kebijakan Pendidikan dalam rangka Membangun Budaya Sekolah Aman dan Nyaman: Analisis Perbandingan Permendikbudristek Nomor 46 Tahun 2023 dan Permendikdasmen Nomor 6 Tahun 2026 - Kosasih Ali Abu Bakar; Oki Setiana Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research discusses about the transformation of educational policy of character building in Indonesia, to compare between Minister of Education, Culture, Research, and Technology Regulation Number 46 of 2023 and Minister of Primary and Secondary Education Regulation Number 6 of 2026. The purpose of this study is to analyze the differences between the two policies in terms of policy substance, paradigm shifts, and their implications for educational practices in Indonesia. The method used is a literature review with a comparative-conceptual analysis. The findings show a paradigm shift from a reactive approach to a preventive and transformational approach, from a sectoral approach to a holistic one, from a structural approach to a collaborative one, and from an administrative approach to a value-based approach. The implications of this policy transformation require strengthening the roles of teachers, school principals, students, families, communities, and media as part of the educational ecosystem. Thus, educational policy functions not only as a regulatory instrument but also as a means of social transformation in building a sustainable, humanistic, and character-oriented educational environment for students.